PENGAKUAN PENDAPATAN DAN BEBAN PADA PT. IMM SAAT MASA PANDEMI 2020-2021 - Puteh, Rio Nanda; Sahusilawane, Wildoms (Politeknik Negeri Ambon, 2023)
COVID-19 has a broad impact on the Indonesian economy. One is in the automotive sector, which suffers negative consequences such as inhibiting production processes due to social constraints that lead to a shortage of auto components and rising sales prices. Vulnerable market conditions make rising component prices a serious problem that must be addressed with good planning in order to avoid prolonged losses. In the mitodst of an unstable economy, recognition of income and burden becomes very important and crucial. The company’s policy plays a decisive role in recognising accrual profits and accrual burdens, affecting the financial statements, especially the company's profit and loss report. This study aims to explain and analyse the recognition of PT's income and burden. IMM during the early pandemic period in 2020 and compared it to 2021. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and analysis of PT financial statements. by IMM. To improve the validity of the research, the triangulation technique of the source is used in the financial statements for 2020 and 2021 PT by IMM. The results of this study showed that PT. IMM records the recognition of revenue and expenses based on referring to PSAK rather than SAK ETAP, and is recognized using the accrual basis method where the financial statements in 2021 demonstrate an increase and better compared to the year 2020.